Motives for Assuming and Continuing Family Care: Family Caregivers’ Perspective - Charenkova, Jūratė (Socialinė teorija, empirija, politika ir praktika, 2022)
Studies have shown that the circumstances and motivation for becoming a caregiver are closely related to the caregiver’s well-being and the quality of care provided, which, in turn, affects the quality of life of the person receiving the care. This article aimed to reveal the motives behind decisions related to an aging relative’s care – motives to assume the caregiving duties and motives to remain in the caregiving role. In total, seven family caregivers participated in semi-structured interviews. Two main themes related to caregiving motivation were revealed: (1) motives to assume the caregiver role, and (2) motives to continue with family care. The results of the research were interpreted using the perspective of self-determination theory (Ryan & Deci, 2000; 2017). This study revealed that key motivational drivers of caregiving decisions were associated with the satisfaction of the three basic psychological needs – autonomy, competence, and relatedness. Meeting these needs in the context of caregiving not only strengthened the caregivers’ motivation to take on the caregiving role but also motivated them to continue with family care, even after the autonomy of care recipients had increased significantly.
Keywords: older people; family care; self-determination; motivation; well-being